2019
DOI: 10.3892/etm.2019.7553
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity mechanism of sevoflurane in neural stem cells of rats through DNA methylation

Abstract: The present study investigated the influence of sevoflurane on the cytotoxicity of neural stem cells of rats and deoxyribonucleic acid (DNA) methylation, and analyzed the correlation between degree of methylation and neurotoxicity of sevoflurane. Ten healthy Sprague-Dawley rats aged 6–8 weeks were randomly selected. The neural stem cells in the hippocampus of rats were isolated, followed by multiplication culture and induced differentiation. The nerve-related factors were observed and detected under a microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A recent study showed that Sev also affected the neurogenesis and differentiation to relieve brain development by inhibiting cell cycle and DNA methylation of NSCs in fetal or young mice. 16,17 These findings suggested a functional connection between NSCs or neuron damage and Sev. However, it remains largely unknown how Sev could affect the NSCs growth and differentiation and further damage neuron function, inducing cognitive impairment in young mice.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent study showed that Sev also affected the neurogenesis and differentiation to relieve brain development by inhibiting cell cycle and DNA methylation of NSCs in fetal or young mice. 16,17 These findings suggested a functional connection between NSCs or neuron damage and Sev. However, it remains largely unknown how Sev could affect the NSCs growth and differentiation and further damage neuron function, inducing cognitive impairment in young mice.…”
Section: Introductionmentioning
confidence: 85%
“…NSCs and NPCs have the potential to differentiate into neurons, astrocytes, and oligodendrocytes to produce a large number of mature brain cells. A recent study showed that Sev also affected the neurogenesis and differentiation to relieve brain development by inhibiting cell cycle and DNA methylation of NSCs in fetal or young mice 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…The value of the conclusions is to provide guidance for further research. Representative procedures and experimental methods are as follows 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 (Figure 1 and Table 1 ).…”
Section: Experimental Models and Experimental Methodsmentioning
confidence: 99%
“…Sevoflurane is a halogenated ether anesthetic that induces and maintains general anesthesia. The concentration of sevoflurane can produce certain cytotoxicity by affecting the methylation degree of NSCs in rats 23 . Repeated exposure to chronic sevoflurane leads to early differentiation of NSCs through the miR‐410‐3p/ATN1 pathway, 70 reducing their pluripotency, reserves, and hypoxia tolerance 71 .…”
Section: Effects Of Anesthetic Drugs On Nscs and Their Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation